'Since they are here in Czechia, they should talk in Czech'. Ethnicity in peer groups at school. Issue 1 (2nd January 2021) - Obrovská, Jana; Jarkovská, Lucie; Lišková, Kateřina
ABSTRACT: Classrooms in Czechia are changing. What used to be a relatively ethnically homogeneous environment changed after 1989 and became much more diverse. How are children, both of Czech, as well as migrant origin, coping? What strategies do they use to negotiate their everyday lives in the classroom? We conducted an ethnographic study in two classes of one multicultural Czech elementary school and used an inductive analytical strategy. While the fifth grade was peaceful, the ninth graders were at war regarding language issues. We analysed ninth graders' narratives of how this situation came into being and their explanations of whose attitudes needed to change. We identified strong pressure to fit in, exerted not only by majority classmates but also by some pupils with migrant backgrounds. In contrast, the fifth grade class revealed migrant children's successful strategies of fitting in, which included helpfulness towards classmates, the development of strong social capital and compliance with authority. In ethnically heterogeneous classrooms, we identified a homogenising push to fit in and negative sanctions for standing out.